Pinkan Mambo’s Donuts: Consumer Perceptions Of Product Personal Branding Strategies - Vickry febrian; Siti khumayah; Dian andriany (CV. ITTC INDONESIA, 2026)
The rapid expansion of social media has transformed the way public figures market products and engage with audiences. This study explores how Pinkan Mambo’s personal branding strategy on social media shapes consumer perceptions of Donat Pinkan Mambo. A qualitative case study approach was employed, involving digital observation, documentation, and in-depth interviews with six informants. The findings reveal that consistent self-representation, personal storytelling, and interactive communication contribute to consumers’ cognitive understanding, emotional attachment, and purchase intention. The study concludes that personal branding operates not merely as promotional exposure but as a symbolic mechanism influencing how consumers interpret and evaluate products.